A study of the competencies of ICT usage among Diploma in Public Administration students in their studies: a study in Universiti Teknologi MARA (UiTM) Malacca - Kamal Din, Siti Anum Satia; Mohamed Yusof, Siti Bashirah (2006)
Technology permeates our society. But do institutions of higher education adequately prepare students to use this technology? The definition of computer literacy continues to change as technological innovations are adopted by the marketplace. The specific technology installed in any university setting constantly changes in both sophistication and function. The challenge for universities is to ensure their students meet a minimum level of competency when using new constantly changing technology. As this will be helpful for the students in finding future jobs. This study examines the level of competency of DPA students in using their basic computer skills in the course of the program.